The complete equation is x^2 - 4x + (-2) = (-2)^2
The equation is given as:
x^2 - 4x + __ = (__)^2
_____________________________
Take the coefficient of x
k = -4
Divide by 2
k/2 = -4/2
k/2 = -2
Square both sides
(k/2)^2 = (-2)^2
_____________________________
Add the result of the above computation to both sides of x^2 - 4x + __ = (__)^2
So, we have:
x^2 - 4x + (-2) = (-2)^2
Hence, the complete equation is x^2 - 4x + (-2) = (-2)^2
Read more about completing the square at:
https://brainly.com/question/16483306
#SPJ1